(untitled) (Alexandria, Va., 2002)
English for Specific Purposes (ESP) is an exciting movement in language education. It is opening up rich opportunities for English teachers and researchers in new professional domains. Whatever one's teaching context, these case studies offer much to learn about curriculum and course planning, implementation, and evaluation.
Keywords: Tiếng Anh,Tiếng Anh,English language,English language; Foreign speakers.,Study and teaching (Higher),Người nói ngoại ngữ,Học tập và giảng dạy (Cao hơn),Study and teaching (Higher),Foreign speakers,Tiếng Anh thương mại,Học tập và giảng dạy